An Investigation into the Role of Coping in Preventing Depression Associated with Perfectionism in Preadolescent Children - Dry, S.; Kane, Robert; Rooney, Rosanna (Frontiers Research Foundation, 2015)
The relationships between self-oriented and socially prescribed perfectionism (SPP) and maladaptive and adaptive coping strategies and their collective impact on depression symptoms were examined in the context of a randomized controlled universal trial of the Aussie Optimism Positive Thinking Skills Program. Five hundred and forty-one children aged 8-12 completed a battery of self-reports, of which responses for measures of depression symptoms, perfectionism, and coping strategies were examined for the purposes of this study. Structural equation modeling tested whether coping mediated the effects of perfectionism on depression. Results indicated that SPP had both a direct and an indirect relationship with depression symptoms through a moderate association with maladaptive coping. Implications for prevention of depression were discussed and recommendations for future research were proposed.